Ville à vendre Voie libérale et privatisation du secteur de l'habitat à Chennai (Inde) - Auclair, Christine (Collection Sciences Sociales, 1998)
During the 1980's, a number of countries started liberalizing their housing policies. From attempting to provide housing directly the State took on an "enabling" role, one which aims at facilitating the activities of the private sector. The privatization of the housing sector, as a process of retreat of the State, has major implications, with new economic and social policies, particularly the development of new strategies of access to housing by different socio-economic groups. The "enabling approach" is presented as the solution to meet the challenge of shelter provision, especially in developing countries, experiencing important economic adjustments. This is the case of India, this "demographic" giant, where housing constitutes a major development issue, particularly in large cities. Despite the implementation of an important institutional framework, intended to contain social inequality, the Government of India has not found an adequate response to shelter needs. In this context, the question is whether privatization will be able to provide conditions for sustainable shelter? The objective of this research enquiry is to analyze the prospects of the so called "enabling" approach, by examining the past state "interventionist" framework, the implementation of the privatization in the Indian context, and its impacts in cities.